Analisis Swot Sebagai Landasan Dalam Menentukan Strategi Pemasaran Pada Rameyza Tour & Travel Bondowoso - Dwi Andri Risqianto; Imam Suroso; Ridwan Iskandar (RELASI : JURNAL EKONOMI, 2018)
This study aims to determine alternative marketing strategies and their implications for marketing Rameyza Tour & Travel Branch Bondowoso. Analytical method used is SWOT analysis. Internal factor analysis (IFAS) and external factors (EFAS) are used to determine the firm's position through the quadrant table. IE Metrics and SWOT Metrics are used to determine marketing strategic formulations that are appropriate to current corporate conditions. The results showed that Rameyza Tour & Travel Bondowoso Branch is in quadrant V, this means marketing strategy that must be done is horizontal innovation strategy that is in applying its strategy focused on the addition or improvement to the implementation of the function of each activity in the business unit of Tour & Travel service . In the description of SWOT metrics, there are several alternative marketing strategies such as: 1) Improving partnership with institutions and schools, 2) Increasing online promotion to expand market, 3) Promoting promotion especially service for private tour and attracting foreign tourists. 4) Maintaining continuous service quality, 5) Expanding the market by adding products sold, such as aircraft ticketing service, and railways as a productdiversified form. Keywords: SWOT, Marketing, Strategies